1994
DOI: 10.1111/j.1470-8744.1994.tb00321.x
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of biotinylated red blood cells

Abstract: Biotinylation of intact mammalian red blood cells (RBC) was performed either by attachment to the amino groups by means of biotin N-hydrosuccinimide ester (NHS-biotin) or by oxidation of the induced aldehyde groups of the RBC membrane by biotin hydrazide. Comparison of these different procedures showed that biotinylation by NHS-biotin provided the highest cell recovery (> 90%), the binding of approximately 1000 biotin molecules/cell (on mouse RBC) and the 24 h survival in circulation was unaffected. In contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 0 publications
1
19
0
Order By: Relevance
“…1 B, D), showing the safeguard of the physiological membrane protein turnover. Consistently with this last observation, several investigators reported that the biotinylation reagents do not seem cytotoxic in in vitro and in vivo experimental models [18,20,21].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…1 B, D), showing the safeguard of the physiological membrane protein turnover. Consistently with this last observation, several investigators reported that the biotinylation reagents do not seem cytotoxic in in vitro and in vivo experimental models [18,20,21].…”
Section: Discussionsupporting
confidence: 72%
“…Avidin-biotin interaction has been largely exploited for "protein detection" techniques (in immunology, histochemistry, in situ hybridization, affinity chromatography and other areas) as well as in pioneer techniques aimed at improving cell adhesion or drug delivery. Of these, biotinylation of TNF-α was proposed as an approach to direct the cytokine to the membrane of melanoma cells [17], and biotinylation of red blood cells as a potential antigen delivery system via the biotin-avidin-biotin bridge [18]. An interesting report demonstrates the safety and specificity of red blood cell delivery of HIV-Tat as a step in the design of a new anti-HIV vaccine [19].…”
Section: Discussionmentioning
confidence: 99%
“…This result indicates that detachment of b-IgG may occur in the pulmonary vasculature, enriched by capillaries. In contrast, splenic this section document that b-IgG/SA/b 23 -RBC circulate amined for the possibility of selective delivery of antigens to immunocompetent cells (10) and for the elimination of circulating molecules and particles from the bloodstream (11). Therefore, SA-mediated attachment of biotinylated antibodies is a key aspect in the design of immunoerythrocytes for drug targeting, targeted immunization, and selective blood clearance.…”
mentioning
confidence: 90%
“…Iodogen was obtained from Pierce (Rockford, IL). immunization (10)) and specific elimination of circulating pathogens from blood (11).…”
mentioning
confidence: 99%
“…A human leukocyte antigen (HLA) A0201 restricted epitope, deriving from HIV-1 protease (PR 75–84 wt , VLVGPTPVNI) and a mutant variant (PR 75–84 d.mut ) harboring two drug resistance mutations, V82F and I84V were resuspended in phosphate buffered saline (PBS), biotinylated and coupled to syngeneic erythrocytes by avidin-biotin bridges [5,9-12]. The amount of peptide bound to the red blood cells was estimated to 25 ng/mL blood [7,9].…”
Section: Resultsmentioning
confidence: 99%